The Ability of Listening to Fairytale through the Guessing Word Strategy of Junior High School Students - Marlia Muklim; Abd Rahim Ruspa; Nirwana Tauchid; Supriani Supriani; Hafirah Patang (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The purpose of this study was to describe the ability to listen to fairy tales through the application of a guessing strategy for class VII students of SMP Negeri 3 Masamba, North Luwu Regency. The type of research used was descriptive quantitative. The sample in the study amounted to 18 students. While the data analysis technique used was simple statistics based on the enthusiasm of students in learning. Based on the results of the study that in the initial test before being given treatment, the sample who obtained a score of 75 was 2 students or 11.12% and students who scored <75 were 16 students or 88.88%. Meanwhile, in the final test, after being given treatment, the sample received a score of 75 as many as 14 students or 77.78% and students who scored <75 were 4 students or 22.22%. In accordance with the description of the results of the study, it can be concluded that the ability to listen to fairy tales through the application of a guessing strategy for class VII students of SMP Negeri 3 Masamba, North Luwu Regency is adequate after being given a final test with the application of a guessing strategy.